(untitled) (Journal of Medicine, 2025)
Background: Mucormycosis is a rapidly progressing and deadly form of fungal infection. It poses a significant threat to patients with uncontrolled diabetes or other underlying systemic conditions.This infection can manifest in various forms, including rhino-cerebral, pulmonary, gastrointestinal, cutaneous, or disseminated types. The underlying conditions can affect the clinical presentation and often delay diagnosis, leading to poor outcomes. A black necrotic eschar is the defining characteristic of mucormycosis. Most cases are considered acute surgical emergencies. Case Details: We report a case of rhino-cerebral mucormycosis in a 64-year-old diabetic patient who presented with sinusitis and occasional nasal bleeding. Gradually, he developed cavernous sinus thrombosis, superior sagittal sinus thrombosis, and bilateral frontal lobe infarcts. Unfortunately, the patient died due to delayed diagnosis and initiation of definitive treatment. Conclusion: Early diagnosis is crucial for survival and the reduction of complications. Clinician awareness, swift treatment initiation, and timely surgical intervention are effective strategies for managing the disease. J MEDICINE 2025; 26(2): 152-155